Zabiegi dyplomacji amerykańskiej na rzecz zwołania Genewskiej Konferencji Morskiej w 1927 roku - Żurawski vel Grajewski, Przemysław (Acta Universitatis Lodziensis. Folia Historica, 1995)
This article presents the reasons and the results of the action of the US diplomacy aimed at convocation of the Geneva Naval Conference in 1927. The lack of any real achievments of the Preparatory Commission for the Disarmament Conference that from the American point of view had proved to be a fruitless deliberations of the European powers concentrated on the matters of no interest to the United States made the Coolidge administration take up the initiative to convoce a separate naval disarmement conference. There were two main reasons why Washington launched the action to that effect: Republican administration needed a spectacular success before the presidential elections in the United States that were to be in 1928. The United States were interested in the control of the naval armaments exclusively. Land disarmament was considered as a regional (European) problem and Washington did not want to be involved in the quarrel of the powers of the old continent. The main aim of the American initiative was to excede the rules adopted in the Washington Treaty in 1922 to the classes of vessels that were not covered by that agreement, i.e. the US government wanted to established the 5-5-3 ratio among the US, the UK and Japan not only for capital ships and aircraft carriers as it had been done in Washington but also for all the auxiliary vessels (cruisers, destroyers and submarines). President Coolidge had invited all the five powers - signatores to the Washington Treaty (the USA, the UK, Japan, France and Italy) still Paris and Rome rejected the invitation. France opposed the idea to base the naval negotiations on the tonnage/class rule which was an immanent one of the American proposal and Italy was not interested in the negotiations without France. For the USA the participation of those two minor naval powers in the conference was important only as far as it could influence the British responce to the American initiative. As a result the Americans easily accepted the idea of Three Powers Naval Conference. Very good experiences of cooperation among the American, British and Japanese delegations in the Preparatory Commission created a misleading impression of mutual understanding of the intentions of the respective powers. This resulted in the lack of any serious preparations to the conference. The place of the conference (Geneva) and the fact that the American representatives to it were appointed among the US delegates to the Preparatory Commission was caused by the Coolidge’s intention not to question the authority of that Commission. Being overanxious to obtain a success becouse of the electoral reasons the US diplomacy acted in hurry and as a result began the negotiations illprepared to them.